-4(x-4)=-3(x-7)-4

Simple and best practice solution for -4(x-4)=-3(x-7)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x-4)=-3(x-7)-4 equation:


Simplifying
-4(x + -4) = -3(x + -7) + -4

Reorder the terms:
-4(-4 + x) = -3(x + -7) + -4
(-4 * -4 + x * -4) = -3(x + -7) + -4
(16 + -4x) = -3(x + -7) + -4

Reorder the terms:
16 + -4x = -3(-7 + x) + -4
16 + -4x = (-7 * -3 + x * -3) + -4
16 + -4x = (21 + -3x) + -4

Reorder the terms:
16 + -4x = 21 + -4 + -3x

Combine like terms: 21 + -4 = 17
16 + -4x = 17 + -3x

Solving
16 + -4x = 17 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
16 + -4x + 3x = 17 + -3x + 3x

Combine like terms: -4x + 3x = -1x
16 + -1x = 17 + -3x + 3x

Combine like terms: -3x + 3x = 0
16 + -1x = 17 + 0
16 + -1x = 17

Add '-16' to each side of the equation.
16 + -16 + -1x = 17 + -16

Combine like terms: 16 + -16 = 0
0 + -1x = 17 + -16
-1x = 17 + -16

Combine like terms: 17 + -16 = 1
-1x = 1

Divide each side by '-1'.
x = -1

Simplifying
x = -1

See similar equations:

| 5+10-5*2+45+2x=400 | | 40X+(1.5X)(5)=661 | | 8p-19=-28+7p | | 15+4a^2=2a^3-5 | | 4r-13=-15+5r | | -6(8-5r)=-r-6(1-4r) | | 5*2+10-5x=205 | | x+2x-4x=16 | | 5*2+5x=18 | | 6*2+2x=12 | | 16x+44=0 | | 3k^2-28=-17 | | 3x^2-12x+39=5 | | X+7z=24 | | 7p^2-16p-21=-6 | | 9+81= | | 50a^2*41=2a^4+5000 | | 1500/x | | 50x^2*41=2x^4+5000 | | 9n^2-4=572 | | 0=x(6x-18) | | Y=x(6x-18) | | X-.05x=360640 | | -5(5b-4)+2(9b+2)= | | 9(z+2)-4z(3z+5)= | | 4=-16t^2+96t+4 | | 30*0.2x=45+3(x) | | 3p(8+2p)-p(2p-3)= | | 4/7t-1/14t=t-17/2 | | b(3+3b)-b(2b-3)= | | 0.25m+0.5+0.75m=1.5m | | -2(w+14)=-12 |

Equations solver categories